Perinatal depression: Factors affecting help-seeking behaviours in asylum seeking and refugee women. A systematic review - Amanda Firth; Melanie Haith-Cooper; Josie Dickerson; Andrew Hart (Elsevier, 2022)
Purpose: Perinatal depression is one of the most commonly diagnosed mental health conditions in the general maternity population but whilst the prevalence is thought to be much higher in asylum seeking and refugee (AS&R) women, it is less frequently identified and diagnosed by health care professionals. Method: A systematic review was undertaken to address 'what factors influence help-seeking behaviours in asylum seeking and refugee women with symptoms of perinatal depression'. The review focussed on women accessing care in high income countries. 12 studies met the eligibility criteria and a narrative synthesis was undertaken resulting in two main themes: women's perceptions of depression and access to healthcare and support services. Results: Findings indicated that many of the influences on help-seeking were also present in the general population and women from ethnic minority populations, with the exception of migration experiences; but that women from a AS&R background may experience more of these barriers, exacerbating inequality in access to and engagement with healthcare. Conclusion: Further research is needed to provide more detailed insight into the experiences of asylum seeking and refugee women to identify ways that barriers in help-seeking can be addressed.